An Active Contour For Underwater Target Tracking And Navigation. - Muhammad Asif, Muhammad Asif; Arshad, Mohd Rizal; Yahya, Abid (2006)
This paper presents a vision based tracking system for routine underwater pipeline or cable inspection for autonomous underwater vehicles (AUV’s).